TINJAUAN HUKUM ISLAM TERHADAP PRODUK AR-RAHN USAHA MIKRO HAJI PEGADAIAN - Qurotul Aini (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2022)
Ar-rahn Hajj Micro Business is one of the pawnshop products that is guided by the National Sharia Council Fatwa Number: 92/DSN-MUI/IV/2014 concerning Financing accompanied by Rahn. A very urgent problem that makes researchers interested in conducting research is the indication of legal hilah in the implementation of the Arrum Haji contract itself. Therefore, the researcher assumes that the implementation of the Arrum Haji product at Pegadaian is the same as the implementation of the Hajj bailout product at Islamic Banks. The type of research used is a combination of library research and field research (mix-method). The nature of the research is analytical exploratory and the approach used is a conceptual approach. The results showed that (1) the loan agreement accompanied by Rahn in the Arrum Haji Pegadaian product was in accordance with the requirements in the sharia agreement law. However, there is one condition that has not been fulfilled because the contract is made and signed before the customer registers for Hajj, so that one of the marhun cannot be submitted, namely the document marhun. (2) there is a legal hilah carried out in the process of determining mu'nah, this can be seen in the engineering carried out by sharia pawnshops which indirectly sharia pawnshops take advantage of loans given to customers, namely 0.95% of the estimated value of marhun and deposited along with monthly principal installments for all selected term options. (3) In terms of benefits, the implementation of Arrum Haji creates something that becomes an intermediary towards takalluf actions and the presence of Arrum Haji products also has the potential to cause the queue for Hajj to be even longer.